Wages and Commuting: Quasi‐natural Experiments' Evidence from Firms that Relocate. (19th December 2013) - Mulalic, Ismir; Van Ommeren, Jos N.; Pilegaard, Ninette
<x xml:space="preserve">Abstract</x> We examine individual‐level compensating differentials for commuting distance in a quasi‐natural experiment setting by examining how wages respond to changes in commuting distance induced by firm relocations. This set‐up enables us to test for the relevance of job search frictions within labour market models. Due to the quasi‐experimental set‐up, we are able to avoid a range of endogeneity issues. We demonstrate that a 1 km increase in commuting distance induces an almost negligible wage increase in the year after the relocation but a more substantial wage increase of about 0.15% three years later.